Kondratieff Waves and Types of Capitalism - Norkus, Zenonas (Sociologija. Mintis ir veiksmas, 2010)
The paper presents new evolutionary typology of capitalism in outline. This typology is grounded in the Marxist conception of the mode of production that considers as distinguishing features of a mode of production the character of the production forces and that of the property relations for means of production. However, the thesis of K. Marx is rejected that capitalist relation of production are no more adeaquate to production forces. Instead, the view is substantiated that the development of the production forces causes the replacement of one capitalist mode of production by another capitalist mode of production. In the analysis of the development of production forces under capitalism, the ideas of Nikolai Kondratieff and Joseph A. Schumpeter on long business cycles are used. In the development of the production forces since industrial revolution in the late XVIII century, 5 technological economical paradigms are distinguished. Each of them is foundation of a separate capitalist mode of production. 5 capitalist modes of production corresponding to the 5 long Kondratieff waves are main evolutionary types of capitalism. They are (1) local capitalism of individual and family enterprise owners; (2) local capitalism of small and middle closed joint stock companies (corporations); (3) national capitalism of big private corporations; (4) state regulated national capitalism of poblic corporations; (5) globalized transnational capitalism of investition funds. These types can be differentiated into subtypes, like liberal market and coordinated capitalism for type (4). This typology is most adequate for the analysis of the economic life in the advanced countries. In the analysis of the social economic reality from the periphery and semiperiphery of the contemporary world capitalist system, the types of political oligarchic, state and state monopolist capitalism are more useful.